Uso del hidrógeno como fuente alternativa para alimentar pilas de combustible (2018)
This monograph has the purpose of describing the use of hydrogen as an alternative source to fuel fuel cells. Hydrogen in recent years has been cataloged as the fuel of the future due to its high energy efficiency without producing greenhouse gases. This study presents the hydrogen production methods which are classified as conventional and unconventional, the latter being of greater interest to be renewable and friendly to the environment.